Rancang Bangun Sistem Pemantauan Pergeseran dan Kelembapan Tanah Berbasis Telemetri - Nurrokhnim, Muh. Hamzah Tsalis; Andi, Andi; Rakhmadi, Frida Agung (Universitas Andalas, 2025)
A monitoring system for soil movement and moisture using MPU6050 accelerometer sensor and soil moisture sensor has been designed. Changes in acceleration and humidity around the sensor cause changes in the capacitance value of each sensor. The change in capacitance from each sensor is then processed by the microcontroller contained in the Arduino UNO R3 with the Arduino IDE programming language to produce acceleration and humidity data. Data is sent via Radio signal contained in the nRF24L01+ module every 1.2 seconds. The test results show a precision value for acceleration of 95.24% on the X axis, 95.11% on the Y axis, 99.86% on the Z axis and a precision value for humidity measurement of 100%. The test results show that the soil movement and moisture monitoring system can work well and the data sent via radio waves is successful and applicable.